Pembimbingan “Basic English Speaking” di Tingkat Sekolah Madrasah Aliyah Key Lebu Witihama - Ummi Qalsum Arif (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Speaking is one of the important skills in learning English. The success of learning English is also measured by speaking ability. However, this skill is still considered difficult to learn by students. The problem that is often faced in learning English is that students' ability to speak English is still low. This is caused by limited vocabulary and lack of understanding of the structure of the English language. Moreover, students who live in villages are still far from enthusiastic in learning English. To overcome this problem, lecturers conducted community service, especially at the MAS Key Lebu school with the topic of service, namely "Basic English Speaking". This speaking skill learning is carried out using games, pictures and explanations. This service aims to 1) improve students' ability to speak English through games and pictures, 2) change students' mindsets about the importance of learning speaking skills in English, and 3) increase students' confidence in learning a foreign language without having to be ashamed of making mistakes. The results of this activity showed an increase in active student participation, increased vocabulary, and students' courage in expressing opinions using English. It is hoped that this activity can be an initial stimulus in building a culture of English communication in the madrasah environment.